Impact of Non-sedation in Gastrointestinal Conventional Endoscopy Practices in Outpatient Setup - Shaik, Arifa Begum; Srija, Billakuduru; Keerthi, Kalvakollu; Laharika, Ambadipally; Saisree, Malli; Begum, Shaheen; Babu, Sethu (Journal of Pharmacy Practice and Community Medicine)
Background: This study is aimed to evaluate the impact of non-sedation in gastrointestinal conventional endoscopy practices in outpatient setup. The importance of our study is to assess the safety, tolerability of the non-sedation methodology and suggest the benefits of the non-sedation procedures. This study was conducted in endoscopy department of Krishna Institute of Medical Sciences (KIMS). A total of 150 patients were included in the study after acquiring their consent over it. Pregnant, lactating women, Volunteers with less than 18years. Patients with Cardio respiratory problems and recent myocardial infarction were excluded from the study. All the necessary data was collected from the patient record such as case sheets, lab reports, medical history. Required tools and software were used to assess the collected data and results were calculated based on them. Aim: To Evaluate and Study the impact of non-sedation in gastrointestinal conventional endoscopy practices in outpatient setup. Materials and Methods: In the present study, a total 150 subjects undergoing Endoscopy were enrolled as per inclusion and exclusion criteria from the Department of Gastroenterology, Krishna Institute of Medical Sciences (KIMS). Results: Based on post endoscopy complications 70 cases were with Difficulty in swallowing (47%), 2 cases were with Change in speech (1%), 46 cases with Throat pain (31%) and 32 cases were with Vomiting sensation (21%). Based on pre pain score of 86 were little discomfort, 53 were mild pain, 14 for moderate pain and none had severe pain. Based on oxygen saturation levels during endoscopy 36 cases were of SpO2 (100%), 59 cases of SpO2 (98%), 55 cases of SpO2 (97%). Based on pain scale endoscopy, 26 people are in pain before endoscopy, 89 people are in pain during endoscopy, 35 people are in pain after endoscopy. Post endoscopy pain score (sedation) were 87 people has pain after endoscopy (2 hr), 43 people has pain after endoscopy (4 hr), 20 people having pain after endoscopy (6 hr). Conclusion: The present study concludes that patients can also undergo the endoscopy procedures without taking a sedative which decreases the unwanted side effects which are commonly observed with the sedatives and also improve the quality of life of patients and even they need not to be monitered as a follow up for further complications
Keywords: Endoscopy; Gastro Intestinal Tract; Ccolonoscopy; Non sedation; Safety; Tolerability